Observational evidence on the effects of mega-fires on the frequency of hydrogeomorphic hazards. The case of the Peloponnese fires of 2007 in Greece - Diakakis, M.; Nikolopoulos, E.; Mavroulis, S.; Vassilakis, E; Korakaki, E. (Science of The Total Environment, 2017)
Even though rare, mega-fires raging during very dry and windy conditions, record catastrophic impacts on infrastructure, the environment and human life, as well as extremely high suppression and rehabilitation costs. Apart from the direct consequences, mega-fires induce long-term effects in the geomorphological and hydrological processes, influencing environmental factors that in turn can affect the occurrence of other natural hazards, such as floods and mass movement phenomena. This work focuses on the forest fire of 2007 in Peloponnese, Greece that to date corresponds to the largest fire in the country's record that burnt 1773 km2, causing 78 fatalities and very significant damages in property and infrastructure. Specifically, this work examines the occurrence of flood and mass movement phenomena, before and after this mega-fire and analyses different influencing factors to investigate the degree to which the 2007 fire and/or other parameters have affected their frequency. Observational evidence based on several data sources collected during the period 1989–2016 show that the 2007 fire has contributed to an increase of average flood and mass movement events frequency by approximately 3.3 and 5.6 times respectively. Fire affected areas record a substantial increase in the occurrence of both phenomena, presenting a noticeably stronger increase compared to neighbouring areas that have not been affected. Examination of the monthly occurrence of events showed an increase even in months of the year were rainfall intensity presented decreasing trends. Although no major land use changes has been identified and chlorophyll is shown to recover 2 years after the fire incident, differences on the type of vegetation as tall forest has been substituted with lower vegetation are considered significant drivers for the observed increase in flood and mass movement frequency in the fire affected areas.
Keywords: Floods; Forest fires; geomorphology; Hydrogeomorphic; Landslides; Megafires